Platform Work: Concept, Legal Challenges, and Worker Protections in the EU - Alkhaled, Mohamad (Pécsi Munkajogi Közlemények, 2026)
This paper addresses the regulatory challenges and political debates surrounding platform work in Europe, with a particular focus on the legal and institutional context of Hungary. It also reviews evolving definitions of platform work, highlighting the tension between traditional employment classifications and emerging forms of digital work. The analysis addresses the economic and social implications of platform work, including issues of worker protection, social security, and collective representation. In this context, the proposed EU Directive on improving working conditions in platform work (2024) can be considered a significant legislative development aimed at harmonizing employment standards in this atypical type of employment relationship, enhancing transparency, and expanding the scope of collective workers' rights. Furthermore, the study attempts to review some national approaches taken by member states, highlighting various strategies. It concludes with an overview of future legislative prospects, the need for institutional capacity building, and the importance of inclusive stakeholder engagement to ensure that regulatory reforms translate into tangible improvements in working conditions on the ground to achieve greater social protection for platform workers.